Work distribution, methodology and technology for ISD and maintenance : Trends over the last 30 years - Krogstie, John (2006)
The information systems we see around us today are at first sight very different from those that were developed 30 years ago. On the other hand, it seems that we are still struggling with many of the same problems, such as late projects and unfilled customer demands. In this article we present selected data from survey investigations performed by us in 1993, 1998, and 2003 among Norwegian organisations on how they conduct information systems development and maintenance. The investigations looks on many of the same areas as earlier investigations e.g. by Lientz and Swanson in the late 1970’, thus we are able to report on some tendencies of the development in the last 30 years. A major finding is that even if we witness large changes in the implementation technology and methods used, a number of aspects such as overall percentage of time used for maintaining and evolving systems in production compared to time used for development is remarkably stable. The same can be said about the rate of replacement, around 50% of ‘new’ systems to be developed are replacement systems. On the other hand, since we have more complex infrastructures supporting the information systems, more and more of the resources are used for other tasks such as operations and usersupport. Less and less time is available for providing new information systems support in organisation